Three-Year Impacts Of The Affordable Care Act: Improved Medical Care And Health Among Low-Income Adults - Sommers, Benjamin D.; Maylone, Bethany; Blendon, Robert J.; Orav, E. John; Epstein, Arnold M. (Health Affairs, 2017)
Major policy uncertainty continues to surround the Affordable Care Act (ACA) at both the state and federal levels. We assessed changes in health care use and self-reported health after three years of the ACA's coverage expansion, using survey data collected from low-income adults through the end of 2016 in three states: Kentucky, which expanded Medicaid; Arkansas, which expanded private insurance to low-income adults using the federal Marketplace; and Texas, which did not expand coverage. We used a difference-in-differences model with a control group and an instrumental variables model to provide individual-level estimates of the effects of gaining insurance. By the end of 2016 the uninsurance rate in the two expansion states had dropped by more than 20 percentage points relative to the nonexpansion state. For uninsured people gaining coverage, this change was associated with a 41-percentage-point increase in having a usual source of care, a $337 reduction in annual out-of-pocket spending, significant increases in preventive health visits and glucose testing, and a 23-percentage-point increase in "excellent" self-reported health. Among adults with chronic conditions, we found improvements in affordability of care, regular care for those conditions, medication adherence, and self-reported health.